In Vitro Antifungal Activity of Three Synthetic Peptides against Candida auris and Other Candida Species of Medical Importance - Richar Torres; Adriana Barreto-Santamaría; Gabriela Arévalo-Pinzón; Carolina Firacative; Beatriz L. Gómez; Patricia Escandón; Manuel Alfonso Patarroyo; Julián E. Muñoz (MDPI AG, 2023)
Candidiasis is an opportunistic infection affecting immunosuppressed and hospitalized patients, with mortality rates approaching 40% in Colombia. The growing pharmacological resistance of Candida species and the emergence of multidrug-resistant Candida auris are major public health problems. Therefore, different antimicrobial peptides (AMPs) are being investigated as therapeutic alternatives to control candidiasis effectively and safely. This work aimed to evaluate the in vitro antifungal activity of three synthetic AMPs, PNR20, PNR20-1, and 35409, against ATCC reference strains of Candida albicans, Candida glabrata, Candida parapsilosis, Candida krusei, and Candida tropicalis, and clinical isolates of C. auris. Antifungal susceptibility testing, determined by broth microdilution, showed that the AMPs have antifungal activity against planktonic cells of all Candida species evaluated. In C. auris and C. albicans, the peptides had an effect on biofilm formation and cell viability, as determined by the XTT assay and flow cytometry, respectively. Also, morphological alterations in the membrane and at the intracellular level of these species were induced by the peptides, as observed by transmission electron microscopy. In vitro, the AMPs had no cytotoxicity against L929 murine fibroblasts. Our results showed that the evaluated AMPs are potential therapeutic alternatives against the most important Candida species in Colombia and the world.